International relations of the Spanish Institute of Entomology in its initial period, 1941-1967 - A. Gomis; C. Martín-Albadalejo (SHILAP, 2017)
The Spanish Institute of Entomology (IEE) was established in 1941 at a time when Spain suffered international isolation and in which the community of naturalists, and particularly entomologists, had been undermined by the exile of many of Spain’s most famous researchers after the Spanish Civil War (1936-1939). Entomologists of the IEE (including Gonzalo Ceballos, Eduardo Zarco, Ramón Agenjo and Eugenio Morales) gradually restored international relations with entomologists around the world, resulting in the publication of scientific papers by notable foreign entomologists in the three series of publications of the IEE (Eos, Graellsia and Trabajos del Instituto Español de Entomología). Scientific contacts with international centres and colleagues returned to normal, with members of the Institute participating in the International Congresses of Entomology held in Stockholm (1948), Amsterdam (1951) and Vienna (1960) and various meetings of the International Commission for Biological Control. The extended stay of several IEE researchers in overseas centres also helped to rebuild scientific relations that had been damaged by the Spanish civil war.